2021
DOI: 10.1186/s13722-021-00267-1
|View full text |Cite
|
Sign up to set email alerts
|

Care-engaged individuals with polysubstance use in Northeastern US are undertreated for methamphetamine use disorder: a retrospective cohort study

Abstract: Background Stimulant use has increased across the US, with concomitant opioid and methamphetamine use doubling between 2011 and 2017. Shifting patterns of polysubstance use have led to rising psychostimulant-involved deaths. While it is known that individuals who use methamphetamine require greater access to treatment, there is still little known about methamphetamine use and treatment among individuals who are already engaged in outpatient substance use treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Of note is that similar to the literature, 17 the majority of the patients had other SUDs such as opioid use disorder in addition to METH (87%). In fact, only a minority of cases had only METH use as a presenting disorder making it difficult to assess the impact of the protocol on METH alone.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Of note is that similar to the literature, 17 the majority of the patients had other SUDs such as opioid use disorder in addition to METH (87%). In fact, only a minority of cases had only METH use as a presenting disorder making it difficult to assess the impact of the protocol on METH alone.…”
Section: Discussionsupporting
confidence: 80%
“…Given recent increases in rates of METH use among people who also use opioids, 3,18 the present sample is generalizable to other acute inpatient settings in which patients with comorbid SUD including METH use present. Recent research characterizing people who use meth METH in the same geographical region found similarly high rates of OUD (94%) as well as single relationship status (75%) and homelessness (85%) 17 . Thus, while the current sample size was small, the METH protocol was implemented with a population characteristically similar to the greater region in terms of polysubstance use and sociodemographic.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Research is catching up, as the number of academic papers on polysubstance use has increased in recent years, from 60 published in 2012 to 289 published in 2022. As compared to use of a single substance, polysubstance use is associated with a higher risk of overdose, undertreatment and poor treatment outcomes such as relapse [1][2][3]. The literature explicitly at the intersection of lived experience and polysubstance use is sparse, but the links between these concepts are clear.…”
Section: Introductionmentioning
confidence: 99%
“…The Southwest region has historically reported high rates of methamphetamine use, yet use is increasing in the Northeast and certain parts of the Midwest. 1 , 4 , 5 , 9 , 10 , 12 - 14 Young adults, 6 , 15 men, 3 , 4 , 16 - 18 and those of low socioeconomic status 1 , 14 , 18 , 19 have historically been associated with higher rates of methamphetamine use. Although these rates have been increasing, trend comparison using national surveys (eg, National Survey on Drug Use and Health—NSDUH) is inconclusive due to changes in the methodology.…”
Section: Introductionmentioning
confidence: 99%